2012
DOI: 10.1167/iovs.11-8484
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Rescue of Rat Retinal Ganglion Cells and Visual Function by AAV-Mediated BDNF Expression after Acute Elevation of Intraocular Pressure

Abstract: AAV-mediated BDNF expression in the rat retina achieved a sustained rescue of RGCs and visual function after an acute elevation of IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 52 publications
0
34
0
1
Order By: Relevance
“…), and the effect could be sustained for up to 70 weeks (Ren et al. ). Brain‐derived neurotrophic factor (BDNF) was also effective in transiently slowing down axotomy‐induced RGC loss (Zhang et al.…”
Section: Neuroprotection Of Physical Exercise In Glaucomamentioning
confidence: 99%
“…), and the effect could be sustained for up to 70 weeks (Ren et al. ). Brain‐derived neurotrophic factor (BDNF) was also effective in transiently slowing down axotomy‐induced RGC loss (Zhang et al.…”
Section: Neuroprotection Of Physical Exercise In Glaucomamentioning
confidence: 99%
“…One study found that the combination of BDNF with AAV-BDNF had increased amount of survived RGCs by up to 97.4%, which was greater than using AAV-BDNF alone. 127 …”
Section: Viral Mediated Bdnf Deliverymentioning
confidence: 99%
“…Retinal ganglion cell counts showed that the loss in the viral-treated eye was significantly decreased and the F-VEP parameters significantly improved up to 9 weeks after the insult. 106 …”
Section: Retinal Ganglion Cell Targeting To Protect Degenerationmentioning
confidence: 99%